MENGUNGKAP CERITA RAKYAT BERDASARKAN TEMUAN BENDA PURBAKALA DI PULAU ORMU KABUPATEN JAYAPURA - Lestari, Ummu Fatimah Ria (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2012)
This paper shows and explains about the Ormu’s folklores based the prehistoric objects on Ormu Island. This paper purposes to show and explain about the Ormu’s folklores based to the prehistoric objects on Ormu Island. This research uses the descriptive method. The technique of this research are the observe technique and library technique. The result of this research; 1) to find three folklores about the prehistoric objects in Ormu Island, and 2) to describe three folklores about the prehistoric objects in Ormu Island. That folklores are; 1) Kisah Raksasa dan Suku Ormu, it was retold by Monika Toto, 2) Raksasa Jahat Penghuni Kampung Ormu, it was retold by Monika Toto, and 3) Terjadinya Pulau Kelapa, it was retold by Monika Toto.